SEVERE HYPERTRIGLYCERIDEMIA IN A NEWLY DIAGNOSED TYPE 1 DIABETES PATIENT WITH DIABETIC KETOACIDOSIS - Ern, Sherlyn Lai Hui; Chwen, Eunice Lau Yi (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Elevated triglycerides are often noticed during periods of insulin deficiency. Severe hypertriglyceridemia (Triglyceride >10 mmol/L) is an uncommon complication of diabetic ketoacidosis (DKA) and is associated with an increased risk of acute pancreatitis. CASE A 14-year-old female student with a history of COVID-19, one month prior, presented with a one-day history of severe abdominal pain and breathlessness. This was preceded by a 2-month history of weight loss of 5 kg. She had severe metabolic acidosis and was intubated due to respiratory distress. Laboratory results showed blood glucose of 19.8 mmol/L, serum ketones of 6.2 mmol/L, pH 6.99 and serum bicarbonate of 5.6 mmol/L. Serum amylase and urine diastase were normal. Her plasma had a “milky” appearance, and her total cholesterol level was 41 mmol/L with a triglyceride (TG) of 199 mmol/L. She was managed in the intensive care unit with fluid resuscitation, dietary restriction, fenofibrate and high-dose insulin infusion of up to 0.2 U/kg/hour. She responded well with TG levels reduced to 7.37 mmol/L on day 2 of admission. Subsequently, she was transitioned to subcutaneous insulin. Her HbA1c reduced from 15.8% to 7.3% over four months, and her TG improved to 0.5 mmol/L. Her anti-islet cell, anti-GAD and anti-insulin IA2 autoantibodies were strongly positive. Thyroid function test and screening for diabetic complications were negative. CONCLUSION Severe hypertriglyceridemia can be effectively managed in the acute situation with high-dose insulin to bring down the triglyceride level. Optimal glycaemic control also plays an important role in maintaining suppressed triglyceride levels.